AN ANALYSIS OF FIGURATIVE LANGUAGE IN EMILY DICKINSON’S POEMS: Personification, Simile, Hyperbole. - Novi Sriwulandari; Arofah Nur Liana Putri (Fakultas Sastra Universitas Gresik, 2021)
This study which is entitled “Figurative Language in Emily Dickinson Poems” focusing on the use of a figurative languiage and categorize it accordance with the types and describe the meaning of figurative language itself. The reseacher choose five poems which have interesting titles and famous works of Emily Dickinson and using intrinsic approach to gain an understanding of the meaning of figurative language in each poem.The data were collected from Emily Dickinson’s poems and focused on the figurative language. The data which have been identified, collected and classified are analyzed descriptively by using intrinsic approach. This study uses the theory of Perrine in his book “Literature, Structure, Sound and Sense”. According to Perrine, figurative language is away to express something beyond the usual way. In his book also describes the types of figurative language such as personification, metaphor, simile, symbol, synecdoche, metonymy, and hyperbole. The result of this study can be summarized as follows : first, in the poems of Emily Dickinson there are three types of figurative language, including : personification, simile, hyperbole. The personification and simile types dominate every poem of Emily Dickinson. Second, the meaning of figurative language used by Emily Dickinson in her poems in general described Emily Dickinson life experience.